Great Recession and Fiscal Squeeze at U.S. Subnational Government Level - Jonas, Jiri. (Washington, D.C. : International Monetary Fund, 2012)
The paper discusses the fiscal impact of the Great Recession of 2007-08 on state and local governments in the United States. It documents the sharp decline in tax revenue and discusses how states responded to close the budget gaps in order to obey the balanced budget provisions. It highligts the procyclical nature of this policy response, provides a brief comparison with subnational policy stances in other advanced economies, and discusses some options for making subnational fiscal policy less procyclical within the framework of current rules.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet